The design of heat extraction system for salinity gradient of solar pond / Normann Syukran Mazlan - Mazlan, Normann Syukran (2020)
In this study, a simple helical type heat exchanger will be designed and analyse to extract heat from the salinity gradient solar pond (SGSP) at UiTM Cawangan Pulau Pinang. This study will show the performance result of heat extraction system in the salinity gradient solar pond with two different design which are Bottom Heat Exchanger (BHE) and Lateral Heat Exchanger (LHE). The main objective of this project is to design and analyse theoretically the performance of heat exchanger in the salinity gradient solar pond. The CATIA software is used to design the heat exchanger to suit the physical condition of constructed SGSP. The type of pipe material for heat exchanger is polyethene. The diameter of the pipe that use was 0.016m with different length for each design. For BHE, the length of the pipe is 12.825 m while the length of pipe for LHE is 28.31m..The effect of parameters such as the available heat in the body of water as well as the mass flow rate of the working fluids were analysed. The temperature of water outlet, the efficiency of both heat exchangers and the rate of heat extraction were the targeted output from this study for both type of heat exchangers. The expected result from this project study is Lateral Heat Exchanger which extracts the available heat in NCZ and LCZ simultaneously has higher efficiency of heat extraction compare to Bottom Heat Exchanger which extracts heat from LCZ only